Synergetic effect of multicomponent additives on limestone when assessed as a thermochemical energy storage material - Møller, Kasper; Berger, Amanda; Paskevicius, Mark; Buckley, Craig (ELSEVIER SCIENCE SA, 2022)
The effect of adding both Al2O3 and ZrO2 to limestone (CaCO3) to enhance the cyclic stability and reaction kinetics of endothermic CO2 desorption and exothermic CO2 absorption is investigated. The formation of CaZrO3 and Ca-Al-O compounds, e.g. CA5Al6O14, is evident, which enables a substantial >80% capacity retention over 50 calcination/carbonation cycles. The additives enable fast reaction kinetics where an 80% energy storage capacity is reached within 20–30 min, which is attributed to the synergetic effect of having both Ca-Zr-O and Ca-Al-O ternary additives present. The inert nature of the formed compounds prevents sintering of the particles, whilst allowing ion migration throughout the crystal structures, catalysing the carbonation reaction.